NEMATODE PARASITES OF RATS FROM KALIMANTAN - Ferza Ayu Saputri; Kartika Dewi; Galuh Tresnani; Yuni Apriyanti; Nanang Supriatna; Yuli S Fitriana; Yuliadi Zamroni (Treubia, 2024)
Rats can serve as a reservoir of diseases because the parasites within rats can be transmitted to humans and other animals. One of the parasites comes from the phylum Nematoda. This study aimed to identify the nematode species found in rats, determine their prevalence and intensity in Kalimantan Island. This study used 20 carcasses of rats from Kalimantan Island stored in the wet collection of MZB (Museum Zoologicum Bogoriense) BRIN Cibinong-Bogor. Identification was carried out by observing and measuring the nematodes found using a light microscope and Scanning Electron Microscope (SEM). The nematode species were then calculated for prevalence and intensity in each host. In this study, four species of nematodes, including Subulura (Murisubulura) andersoni (10% and 11-35), Subuluridae gen. sp. (80% and 1-53), Mastophorus sp. (25% and 1), and Physocephalus sp. (25% and 5), were found. Kalimantan Island is a new record area for S (M.) andersoni, Mastophorus sp. and Physocephalus sp. This needs further research to identify Subuluridae gen.sp. and its distribution area in Indonesia.